2019
DOI: 10.15376/biores.14.3.5162-5170
|View full text |Cite
|
Sign up to set email alerts
|

High-density particleboard made from agro-industrial waste and different adhesives

Abstract: Particleboards were made using particles from sugarcane bagasse and eucalyptus residues of the pulp industry. The particleboard properties were evaluated according to ABNT NBR 14810-1 (2013), ABNT NBR 14810-2 (2013), and ANSI A208.1 (1999) standards, which compared the efficiency of castor oil-based polyurethane resin (PU-Castor) and urea-formaldehyde resin (UF). The particleboards were composed of 60% wood particles and 40% bagasse, with a 10% adhesive dose based on the dry mass of particles. The following pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Sugarcane bagasse was collected at the Vale do Paraná S/A alcohol and sugar mill, being sun-dried until the apparent moisture reached between 10 and 12%. The material was also crushed to obtain a particle size between 4 and 10 mm (Sugahara et al 2019). The resin consisted of a castor oil-based bicomponent polyurethane resin (PU), with polyol (1.1 g/cm 3 ), made from castor oil and polyfunctional isocyanate (1.24 g/cm 3 ) at a 1:1 ratio (polyol and isocyanate) (Ferro et al 2014).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sugarcane bagasse was collected at the Vale do Paraná S/A alcohol and sugar mill, being sun-dried until the apparent moisture reached between 10 and 12%. The material was also crushed to obtain a particle size between 4 and 10 mm (Sugahara et al 2019). The resin consisted of a castor oil-based bicomponent polyurethane resin (PU), with polyol (1.1 g/cm 3 ), made from castor oil and polyfunctional isocyanate (1.24 g/cm 3 ) at a 1:1 ratio (polyol and isocyanate) (Ferro et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The resin consisted of a castor oil-based bicomponent polyurethane resin (PU), with polyol (1.1 g/cm 3 ), made from castor oil and polyfunctional isocyanate (1.24 g/cm 3 ) at a 1:1 ratio (polyol and isocyanate) (Ferro et al 2014). The adhesive content used was 10% relative to the dry mass of particles (Sugahara et al 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A traditional orthogonal test is typically used to study the influence of process parameters on the physical properties of the final panel, as demonstrated by Wu et al (2016). Sugahara et al (2019) manufactured particleboard using bagasse and eucalyptus slag pulp and tested its properties, i.e., the static bending strength, and internal bond strength. It was shown that the use of bagasse and eucalyptus slag in the production of high-density particleboard was feasible.…”
Section: Introductionmentioning
confidence: 99%